Automatic cloth hanger using rain sensor: article - Ahmad, Ahmad Afi Fayyadh; Sam, Rosidah (2012)
This proposal is about designing a model of automatic cloth hanger with box using rain sensor. This design is to help people that have no time to watch for their own cloth hang outdoor. This design is been controlled by the rain sensor and Programmable Logic Control (PLC). If raining, the sensor will sense it and turn the system on. When the rain sensor detects the rain, the cloth hanger is sliding into the box. The box is made from plastics and wood for water proof. After the cloth hanger is slide completely in the box, two plate of the box will automatically close the open space on a top and bottom. This is to make sure the cloths are not wet from the rain. If the rain is stop, the two side of the box that previously close will open and the cloth hanger in the box will slide the cloth hanger out again. The design will repeat the step again if there is a rain. The expected result from this design is it a user friendly and has a value of commercial promotion.